(untitled) (Research, Society and Development, 2022)
Biodiesel is one of the main sources of renewable energy that can be obtained from oils and fats by transesterification. However, biodiesel produced from vegetable oils as a raw material is expensive. Thus, an alternative and inexpensive raw material such as vegetable oil deodorizing distillate (VODD) can be used as a raw material for the production of biodiesel. In this study, technical-economic analyzes were carried out in the biodiesel production process using VODD as raw material and hydrotalcite-hydroxyapatite as heterogeneous catalyst. Four different scenarios were considered for the economic technical evaluation of the biodiesel production process: heterogeneous catalysis, homogeneous catalysis, reduced ethanol flow in the process input stream, and different proportions of the biodiesel:diesel mixture. Biodiesel production presented a positive internal rate of return (IRR), and in comparison, with the minimum attractiveness rate (MAR), it was economically viable based on the sales prices of the revenues practiced. In the sensitivity analyses, it was observed that the catalyst acquisition price was the most critical factor in the economic analysis of the simulated plant. Using different catalysts, a comparative study showed that the heterogeneous catalyst makes the process less expensive with the purification steps. Thus, it can be confirmed that the results obtained from this study can open paths for new developments in the biodiesel process in relation to the use of residual raw material and new materials to be used as catalysts.